A 3D puzzle approach to building protein–DNA structures. Issue 2 (15th March 2017) - Hinton, Deborah M.
ABSTRACT: Despite recent advances in structural analysis, it is still challenging to obtain a high-resolution structure for a complex of RNA polymerase, transcriptional factors, and DNA. However, using biochemical constraints, 3D printed models of available structures, and computer modeling, one can build biologically relevant models of such supramolecular complexes.